Term Length and the Quality of Appointments - Amihai Glazer; Vesa Kanniainen (Center for Economic Studies and ifo Institute (CESifo), 2000)
Consider a principal who appoints an agent. Let the agent potentially serve for a sufficiently long time that one principal is replaced by another over this period. Suppose also that the quality of the agent appointed increases with the effort the incumbent principal devotes to hiring. Then the quality of the appointment may increase with the length of the agent's term. Moreover, policies such as mandatory retirement which increase a prinicpal's concern for output after he leaves office, may induce better hiring.
Keywords: J20; J40; 330; Hiring; tenure; quality of appointment